2022
DOI: 10.3325/cmj.2022.63.176
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of diabetes mellitus type 2 in the setting of hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: Aim To evaluate the effect of diabetes mellitus type 2 (T2DM) on the outcomes after treatment of hepatocellular carcinoma (HCC). Methods PubMed and Cochrane Central Register of Controlled Trials Databases were systematically searched. Three HCC clinical outcomes were explored: death, progressive disease after locoregional therapies, and recurrence. Sub-analysis was performed according to the use of potentially curative (resection, transplantation, termo-ablation) or non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The annual transition probabilities for individuals with HBV infection alone were derived from published literature and are presented in Additional file 1 : Table S1. Previous studies have indicated that individuals with HBV-T2DM comorbidity can experience a faster disease progression than those with HBV infection alone, and they have reported the corresponding relative risks (RRs) [ 17 , 21 24 ]. To estimate the transition probabilities for individuals with HBV-T2DM comorbidity, we multiplied the RRs obtained from previous cohort studies or meta-analyses by the transition probabilities for those with HBV infection alone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The annual transition probabilities for individuals with HBV infection alone were derived from published literature and are presented in Additional file 1 : Table S1. Previous studies have indicated that individuals with HBV-T2DM comorbidity can experience a faster disease progression than those with HBV infection alone, and they have reported the corresponding relative risks (RRs) [ 17 , 21 24 ]. To estimate the transition probabilities for individuals with HBV-T2DM comorbidity, we multiplied the RRs obtained from previous cohort studies or meta-analyses by the transition probabilities for those with HBV infection alone.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of comorbid T2DM can accelerate the progression of severe liver complications in HBV-infected individuals [ 17 ], which may be due to increased levels of free fatty acids, hepatic oxidative stress, and hyperinsulinemia caused by T2DM [ 18 20 ]. Consequently, individuals with HBV infection who also have T2DM are at a higher risk of developing cirrhosis, HCC, liver-related death, and experiencing a worse prognosis compared to those with HBV infection alone [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing incidence of T2DM has become a global public health concern. 4 Increasing evidence suggests that T2DM is an important risk factor for HCC; [5][6][7] however, studies on how DM contributes to the occurrence and progression of HCC are scarce. It is necessary to explore the relationship between T2DM and HCC, particularly the role of T2DM in HCC.…”
Section: Introductionmentioning
confidence: 99%